Pemberian Insektisida Alami dari Ekstrak Nanoemulsi Daun Ketumpang (Tridax procumbens L.) untuk Pengendalian Perilaku dan Kematian Ulat Krop (Crocidolomia pavonana F.) padaTanaman Sawi - Safrida Safrida; Noor Aisah Riski Wulandari; Supriatno Supriatno (Jurnal Ilmu Pertanian Indonesia, 2020)
Ketumpang (Tridax procumbens L.) contains bioactive compounds that can be used as natural insecticides. To reduce particle size, the extracts were prepared using nanoemulsion techniques. This study aims to determine the effect of nanoemulsion of intercropping leaf extract on behavior and mortality of crop caterpillars on mustard plants. This study used an experimental method with a completely randomized design (CRD) consisting of seven treatments and four replications. The treatments consisted of, K- = Administration of nanoemulsion extract at a concentration of 0% (K-), P1 = Administration of nanoemulsion extract at a concentration of 5%, P2 = Administration of nanoemulsion extract at a concentration of 10%, P3 = Administration of nanoemulsion extract at a concentration of 15 %, P4 = Administration of nanoemulsion extract at a concentration of 20%, P5 = Administration of nanoemulsion extract at a concentration of 25%, and K + = Administration of the chemical insecticide deltamethrin at a concentration of 0.04% as a positive control. Data were analyzed using descriptive and analysis of variance, as well as further tests at α=0.05. The results showed that administration of nanoemulsion ketumpang leaf (Tridax procumbens L.) extract caused behavioral changes (eating, resting, and moving) of caterpillar crop which became inactive and increased mortality of crop caterpillar. Nanoemulsion extracts of overlap leaves could be used to control crop caterpillars. Keywords: crop caterpillars, ketumpang leaf, mustard, nanonemulsion